Electronic health records approaches and challenges: a comparison between Malaysia and four East Asian countries - Abd Ghani, Mohd Khanapi; Bali, Rajeev K.; Naguib, Raouf N.G.; Marshall, Ian M.; Wickramasinghe, Nilmini S. (Inderscience Enterprises Ltd, 2008)
An integrated Lifetime Health Record (LHR) is fundamental for achieving seamless and continuous access to patient medical information and for the continuum of care. However, the aim has not yet been fully realised. The efforts are actively progressing around the globe. Every stage of the development of the LHR initiatives had presented peculiar challenges. The best lessons in life are those of someone else's experiences. This paper presents an overview of the development approaches undertaken by four East Asian countries in implementing a national Electronic Health Record (EHR) in the public health system. The major challenges elicited from the review including integration efforts, process reengineering, funding, people, and law and regulation will be presented, compared, discussed and used as lessons learned for the further development of the Malaysian integrated LHR.